E3 Ligase Subunit Fbxo15 and PINK1 Kinase Regulate Cardiolipin Synthase 1 Stability and Mitochondrial Function in Pneumonia - Chen, Bill B. (2014)
Acute lung injury (ALI) is linked to mitochondrial injury, resulting in impaired cellular oxygen utilization; however, it is unknown how these events are linked on the molecular level. Cardiolipin, a mitochondrial-specific lipid, is generated by cardiolipin synthase (CLS1). Here, we show that S. aureus activates a ubiquitin E3 ligase component, Fbxo15, that is sufficient to mediate proteasomal degradation of CLS1 in epithelia, resulting in decreased cardiolipin availability and disrupted mitochondrial function. CLS1 is destabilized by the phosphatase and tensin homolog (PTEN)-induced putative kinase 1 (PINK1), which binds CLS1 to phosphorylate and regulates CLS1 disposal. Like Fbxo15, PINK1 interacts with and regulates levels of CLS1 through a mechanism dependent upon Thr219. S. aureus infection upregulates this Fbxo15-PINK1 pathway to impair mitochondrial integrity, and Pink1 knockout mice are less prone to S. aureus-induced ALI. Thus, ALI-associated disruption of cellular bioenergetics involves bioeffectors that utilize a phosphodegron to elicit ubiquitin-mediated disposal of a key mitochondrial enzyme.